2016
DOI: 10.1002/rcm.7497
|View full text |Cite
|
Sign up to set email alerts
|

Improved removal of volatile organic compounds for laser‐based spectroscopy of water isotopes

Abstract: SPE is an effective, low-cost method for eliminating errors in ethanol-contaminated samples. For samples where methanol is prevalent, combining SPE and MCM is more effective than the use of SPE alone. Hence, SPE treatment alone or in conjunction with MCM is recommended as an effective pre-analysis purification method for water extracted from plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…The 'thick leaf' setting heats up the leaf samples for a longer cycle (600 versus 300 s for the 'normal leaf' setting), in order to extract water from thicker or more sclerophyllous leaves. We found that C. esculenta leaves samples were consistently burned when using the 'thick leaf' setting, which led to carbonization of leaf tissues and the potential release of compounds that might interfere with the water analyser (Chang et al 2016). However, when set on 'normal leaf', the leaf disks did not appear carbonized.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…The 'thick leaf' setting heats up the leaf samples for a longer cycle (600 versus 300 s for the 'normal leaf' setting), in order to extract water from thicker or more sclerophyllous leaves. We found that C. esculenta leaves samples were consistently burned when using the 'thick leaf' setting, which led to carbonization of leaf tissues and the potential release of compounds that might interfere with the water analyser (Chang et al 2016). However, when set on 'normal leaf', the leaf disks did not appear carbonized.…”
Section: Methodsmentioning
confidence: 89%
“…We found that C. esculenta leaves samples were consistently burned when using the ‘thick leaf’ setting, which led to carbonization of leaf tissues and the potential release of compounds that might interfere with the water analyser (Chang et al . ). However, when set on ‘normal leaf’, the leaf disks did not appear carbonized.…”
Section: Methodsmentioning
confidence: 97%
“…The original version of the IM was designed to extract liquid water into a dry nitrogen stream by induction heating, carry the resulting vapor through a ceramic micropyrolysis column heated to 1200°C to pyrolyze organic contaminants, and pass the cleaned vapor directly into an IRIS analyzer . A revised version of the IM was then designed to combust, rather than pyrolyze, the organic contaminants by replacing the ceramic micropyrolysis column with a metal catalyst heated to only 400°C . In a parallel effort, a microwave extraction chamber was designed to extract liquid water into a dry air stream by microwave heating within a sealed vessel, cool the resulting water vapor in a condensation chamber, and carry the cooled vapor directly into an IRIS analyzer .…”
Section: Parameters Used To Diagnose Spectral Interference the Raw Vmentioning
confidence: 99%
“…Three recent studies have evaluated aspects of the performance of the IM. The first two studies examined the micro‐combustion module (MCM), the component of the IM that contains the heated catalyst to oxidize volatile organic compounds to CO 2 . The MCM can be used either within the IM system or downstream of an autosampler and vaporizer system, and these first two studies both used the latter configuration.…”
Section: Parameters Used To Diagnose Spectral Interference the Raw Vmentioning
confidence: 99%
See 1 more Smart Citation